A fermionic portal to a non-abelian dark sector - Belyaev, Alexander; Deandrea, Aldo; Moretti, Stefano; Panizzi, Luca; Ross, Douglas A.; Thongyoi, Nakorn (Frontiers in Physics, 2024)
We introduce a new class of renormalisable models for Dark Matter with a minimal particle content, consisting of a dark SU (2) D gauge sector connected to the Standard Model through a Vector-Like fermion mediator, not requiring a Higgs portal, in which a massive vector boson is the Dark Matter candidate. These models are labelled Fermion Portal Vector Dark Matter (FPVDM). Multiple realisations are possible, depending on the properties of the VL partner and of the scalar potential. One example is discussed in detail. FPVDM models have a large number of applications in collider and non-collider experiments, with their phenomenology depending on the mediator sector.